LANGUAGE CULTURE INTERACTION IN MODERN LINGUISTICS - Majidova Maftuna Murod qizi (International Journal of Literature and Language Studies, 2026)
The interaction between language and culture represents one of the central problems of modern linguistics and interdisciplinary humanities research. Contemporary linguistic theory increasingly rejects the idea of language as an autonomous formal system and instead emphasizes its embeddedness in cultural, cognitive, and social contexts. This article examines the theoretical foundations, historical development, and methodological approaches to studying language–culture interaction in modern linguistics. Particular attention is given to linguaculturology, cognitive linguistics, and ethnolinguistics as key frameworks for understanding how cultural meanings are encoded, transmitted, and transformed through language. The article also explores the role of linguistic worldview, cultural concepts, and culturally marked lexical units in shaping human cognition and communication. Finally, it discusses the implications of language–culture interaction for translation studies, intercultural communication, and language education.